Classificação Internacional de Funcionalidade, Incapacidade e Saúde em mulheres submetidas ao tratamento do câncer de mama - Carvalho, Flávia Nascimento de (2013)
The objective was to evaluate the applicability of the International Classification of Functioning, Disability and Health in women submitted to treatment for breast cancer. To identify and discuss validated assessment instruments in the Brazilian population relevant to the operationalization of the International Classification of Functioning, Disability and Health in women submitted to the curative treatment of breast cancer; To evaluate, through the protocol of selected instruments, the use of the International Classification of Functioning, Disability and Health in women submitted to the curative treatment of breast cancer; To describe the prevalence of functional disability presented by these women; To investigate the quality of life in women who survived breast cancer; Explore the association between functionality and quality of life.